RELATIONSHIP OF LEAKY GUT SYNDROME AND METABOLIC SYNDROME - Helena Vaz Tolloto, Gilce; Saragiotto, Laiz (Health and Society, 2022)
Leaky gut syndrome is characterized by increased intestinal permeability, translocation of compounds such as toxins, lipopolysaccharides and bacteria from the intestinal microbiota involving pro-inflammatory processes, metabolic changes, and imbalance of lipid and lipid homeotase recent research has related increased intestinal permeability to metabolic syndrome, which is characterized mainly by insulin resistance, abdominal obesity, lipid disorders, prothrombotic and pro-inflammatory processes. The objective of this study is to analyze through the literature review the pathophysiological mechanisms and factors involved in the relationship of Leaky gut syndrome and metabolic syndrome. The research included 113 scientific articles published between 2014 and 2021 in Medline/Pubmed, Scielo and Lilacs databases. Were selected, fifity original academic articles, written in English, which were analyzed according to the year of publication, evaluation method, objectives and main results. The increase in intestinal permeability and alteration of the intestinal microbiota involved inflammatory, lipidic processes, alterations in glucose homeostasis and secretion of enteroendocrine peptides among them GLUT2 and GLP-1 evidencing a strong relationship in pathophysiological mechanisms in Leaky Gut syndrome and metabolic syndrome. Even studies in humans is rare, there is an intense interrelationship between microbiota, altered intestinal permeability in Leaky Gut Syndrome and Metabolic Syndrome.